Uncovering Students’ Attitude toward Vlogging Activities in Improving Students’ Speaking Ability - Berlinda Mandasari; Dyah Aminatun (Premise: Journal of English Education and Applied Linguistics, 2019)
The objective of this study is to uncover the students’ attitude toward vlogging activities in improving students’ speaking ability. Participants of this study are 40 students majoring English Education who enrolled in transactional conversation subject at Universitas Teknokrat Indonesia. Research design used in this study is descriptive qualitative. Data were gained through questionnaire exposing students’ attitude toward the subject and students’ attitude toward using vlog to support learning process. There were 11 indicators with 32 questionnaire items. The results of this study reveal that Vlog helps students to understand the materials, improve students’ learning achievement, motivation, creativity, and engagement, provide interesting learning activities, efficient learning, effective learning, and lead students to be confident, independent and critical.